Cathepsin B-activatable cyclic antisense oligonucleotides for cell-specific target gene knockdown in vitro and in vivo - Zhongyu Wang; Xinli Fan; Guanqun Mu; Xiaoran Zhao; Qian Wang; Jing Wang; Xinjing Tang (Elsevier, 2023)
Trigger-activatable antisense oligonucleotides have been widely applied to regulate gene function. Among them, caged cyclic antisense oligonucleotides (cASOs) maintain a specific topology that temporarily inhibits their interaction with target genes. By inserting linkers that respond to cell-specific endogenous stimuli, they can be powerful tools and potential therapeutic agents for specific types of cancer cells with low off-target effects on normal cells. Here, we developed enzyme-activatable cASOs by tethering two terminals of linear antisense oligonucleotides through a cathepsin B (CB) substrate peptide (Gly-Phe-Leu-Gly [GFLG]), which could be efficiently uncaged by CB. CB-activatable cASOs were used to successfully knock down two disease-related endogenous genes in CB-abundant PC-3 tumor cells at the mRNA and protein levels but had much less effect on gene knockdown in CB-deficient human umbilical vein endothelial cell (HUVECs). In addition, reduced nonspecific immunostimulation was found using cASOs compared with their linear counterparts. Further in vivo studies indicated that CB-activatable cASOs showed effective tumor inhibition in PC-3 tumor model mice through downregulation of translationally controlled tumor protein (TCTP) protein in tumors. This study applies endogenous enzyme-activatable cASOs for antitumor therapy in tumor model mice, which demonstrates a promising stimulus-responsive cASO strategy for cell-specific gene knockdown upon endogenous activation and ASO prodrug development.